Novel biofilm-mediated bioprocesses for water purification - Goh, Keng Siang (2017)
Monochloramine (MCA) is widely being used as a residual disinfectant in water distribution system as it is more stable than chlorine and lessens the formation of disinfection by-products (DBPs). In research, MCA are typically prepared right before each experiment as it decays significantly overtime. However, the lack of standardized method for preparing MCA poses potential consequences on their downstream applications. Several preparation protocols were chosen from relevant journals and the performance of MCA produced were analysed. Various types of degradation kinetics associated with MCA were examined and the abiotic and biotic factors were also discussed. Finally, we studied the killing efficacies of MCA prepared to highlight the need of having a standardised preparation protocol.